Education, matching and the allocative value of romance - Alison L. Booth; Melvyn G. Coles (Institute for the Study of Labor (IZA), 2005)
Societies are characterized by customs governing the allocation of non-market goods such as marital partnerships. We explore how such customs affect the educational investment decisions of young singles and the subsequent joint labor supply decisions of partnered couples. We consider two separate matching paradigms for agents with heterogeneous abilities - one where partners marry for money and the other where partners marry for romantic reasons orthogonal to productivity or debt. These generate different investment incentives and therefore have a real impact on the market economy. While marrying for money generates greater investment efficiency, romantic matching generates greater allocative efficiency, since more high ability individuals participate in the labour market. The analysis offers the possibility of explaining cross-country differences in educational investments and labor force participation based on matching regimes.
Keywords: I21; J12; J16; J41; 330; education; participation; matching; marriage; cohabitation; Bildungsinvestition; Lebensgemeinschaft; Eigeninteresse